Comparative Study of Educational Concepts Kh. Hasyim Asy'ari and Kh. Ahmad Dahlan - Taufik, Ahmad; Suhaimi, Firdaus; Ulfah, Mariah; Agustina, Delia Indah (CV ODIS, 2024)
This research is motivated by its contribution to differences in methods and approaches. Even though both have the same goal, namely advancing Islamic education, the methods and approaches they use are different. KH. Hasyim Asy'ari focuses more on traditional education through Islamic boarding schools, while KH. Ahmad Dahlan further integrates modern education with religious education through modern schools. This study discusses and compares the educational concepts proposed by two major figures in the history of Islamic education in Indonesia, KH. Hasyim Asyari and KH. Ahmad Dahlan. This research uses a qualitative approach with a literature study method. The aim of this research is to explore the potential of these two figures for their contribution to education in Indonesia. Where the results show that KH. Hasyim Asyari places greater emphasis on strengthening Islamic traditions and Islamic boarding school education, while KH. Ahmad Dahlan focuses more on modernizing education and integrating general knowledge with Islamic teachings. Even though there are differences in approach, these two figures have made significant contributions in shaping the Islamic education system in Indonesia.